Caracterización de procesos cognitivos de memoria, lenguaje y pensamiento, en estudiantes con bajo y alto rendimiento académico (2012)
This paper presents a characterization of the processes of memory, language and thought of four groups of students with low, medium, high and higher academic achievement among first and fifth grade, aged between 6 and 11 years, in an educational center in Bogotá-Colombia. to 10 sub-tests of the WISC-IV Were applied, to describe these processes. Academic performance was corroborated by school reports. The results were processed using SPSS-19, ANOVA and Tukey's DHS. The most influential aspect is the verbal comprehension scores with a correlation of .718; followed by perceptual reasoning with a correlation of .659, and finally the working memory with a correlation of .577.